Arterial Spin Labeling for the Etiological Workup of Intracerebral Hemorrhage in Children. Issue 1 (January 2022) - Hak, Jean François; Boulouis, Grégoire; Kerleroux, Basile; Benichi, Sandro; Stricker, Sarah; Gariel, Florent; Garzelli, Lorenzo; Meyer, Philippe; Kossorotoff, Manoelle; Boddaert, Nathalie; Vidal, Vincent; Girard, Nadine; et al.
Abstract : Background and Purpose: Pediatric nontraumatic intracerebral hemorrhage accounts for half of stroke in children. Early diagnostic of the causative underlying lesion is the first step toward prevention of hemorrhagic recurrence. We aimed to investigate the performance of arterial spin labeling sequence (ASL) in the acute phase etiological workup for the detection of an arteriovenous shunt (AVS: including malformation and fistula), the most frequent cause of pediatric nontraumatic intracerebral hemorrhage. Methods: Children with a pediatric nontraumatic intracerebral hemorrhage between 2011 and 2019 enrolled in a prospective registry were retrospectively included if they had undergone ASL-magnetic resonance imaging before any etiological treatment. ASL sequences were reviewed using cerebral blood flow maps by 2 raters for the presence of an AVS. The diagnostic performance of ASL was compared with admission computed tomography angiography, other magnetic resonance imaging sequences including contrast-enhanced sequences and subsequent digital subtraction angiography. Results: A total of 121 patients with pediatric nontraumatic intracerebral hemorrhage were included (median age, 9.9 [interquartile range, 5.8–13]; male sex 48.8%) of whom 76 (63%) had a final diagnosis of AVS. Using digital subtraction angiography as an intermediate reference, visual ASL inspection had a sensitivity and a specificity of, respectively, 95.9% (95% CI, 88.5%–99.1%) and 79.0% (95% CI, 54.4%–94.0%). ASL had a sensitivity, specificity, and accuracy of 90.2%, 97.2%, and 92.5%, respectively for the detection of the presence of an AVS, with near perfect interrater agreement (κ=0.963 [95% CI, 0.912–1.0]). The performance of ASL alone was higher than that of other magnetic resonance imaging sequences, individually or combined, and higher than that of computed tomography angiography. Conclusions: ASL has strong diagnostic performance for the detection of AVS in the initial workup of intracerebral hemorrhage in children. If our findings are confirmed in other settings, ASL may be a helpful diagnostic imaging modality for patients with pediatric nontraumatic intracerebral hemorrhage. REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifiers: 3618210420, 2217698. Abstract : Supplemental Digital Content is available in the text.